Neither Preconceptional Weekly Multiple Micronutrient nor Iron–Folic Acid Supplements Affect Birth Size and Gestational Age Compared with a Folic Acid Supplement Alone in Rural Vietnamese Women: A Randomized Controlled Trial. Issue 7 (8th June 2016) - Ramakrishnan, Usha; Nguyen, Phuong H; Gonzalez-Casanova, Ines; Pham, Hoa; Hao, Wei; Nguyen, Hieu; Truong, Truong V; Nguyen, Son; Harding, Kimberly B; Reinhart, Gregory A; Neufeld, Lynnette M; Martorell, Reynaldo
Abstract: Background: Maternal nutritional status before and during early pregnancy plays a critical role in fetal growth and development. The benefits of periconception folic acid (FA) supplementation in the prevention of neural tube defects is well recognized, but the evidence for preconception micronutrient interventions for improving pregnancy outcomes is limited. Objective: This study aimed to evaluate whether preconception supplementation with weekly iron and folic acid (IFA) or multiple micronutrients (MMs) improves birth outcomes compared with FA alone. Methods: We recruited 5011 women of reproductive age in a double-blind, randomized controlled trial in Vietnam and provided weekly supplements containing either 2800 μg FA, 60 mg Fe and 2800 μg FA (IFA), or the same amount of FA and iron plus other MMs until they conceived ( n = 1813). All pregnant women received daily IFA through delivery, and were followed up for birth outcomes, including birth weight, gestational age, preterm delivery and small for gestational age (SGA). Group comparisons were done with the use of ANOVA or chi-square tests for both intention-to-treat ( n = 1599) and per-protocol analyses (women consumed supplements ≥26 wk before conception; n = 824). Effect modification by baseline underweight or anemia status was tested with the use of generalized linear models. Results: The mean age of the women was 26 y, 30% were underweight, and <10% were nulliparous. The groups were similar for most baseline characteristics. The mean ± SD duration of the preconception intervention was 33 ± 25 wk and compliance was high (>90%). Infants born to the 3 groups of women did not differ ( P ≥ 0.05) on mean ± SD birth weight (3076.8 ± 444.5 g) or gestational age (39.2 ± 2.0 wk), or prevalence of SGA (12%), low birth weight (5%) and preterm delivery (10%). There were no significant differences in women who consumed supplements ≥26 wk before conception or by baseline underweight or anemia. Conclusion: Weekly supplementation with MMs or IFA before conception did not affect birth outcomes compared with FA in rural Vietnamese women. The trial was registered at clinicaltrials.gov as NCT01665378.